SHEPWM based new hybrid multilevel inverter topology with reduced switch count - Siddique, Marif Daula; Mekhilef, Saad; Shah, Noraisyah Mohamed; Momon, Mudasir Ahmed; Mustafa, Asif (2019)
In this paper, a new single-phase hybrid multilevel inverter topology is proposed with reduced switch count. The basic unit of the proposed topology is capable of generating 13 levels at the output. A higher number of levels can be generated by extending the basic unit. Two different extensions of the basic unit have been proposed in the paper. The topology consists of a level generation unit (LGU) and the polarity changing unit (PCU). The level generation unit of the proposed topology is based on the series connection of multiple switched dc voltage sources with half and full bridge configurations. Selective Harmonic Elimination PWM (SHEPWM) based switching control technique has been employed for an improved harmonic spectrum. Performance and effectiveness of the proposed topology with the employed SHEPWM control have been substantiated by simulation results and verified by experimental results obtained from a laboratory prototype.